A Review on Polymer Based Antimicrobial Coating (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Antimicrobial coatings have become a key component of the worldwide microbial infection mitigation plan. A wide range of alternatives for designing surfaces with antimicrobial qualities is now accessible, attributed to the recent developments in materials science, biotechnology, and environmental microbiology. Antimicrobial coatings have a big role to control the spread of disease, preventing microbial colonisation on the substrate used in various applications. The antimicrobial coatings could be formed on the substrate by utilizing the polymer with antimicrobial properties or incorporating the antimicrobial agents into the polymer. By manipulating the use of polymers and surrounding conditions, the antimicrobial activity of the coating could be tailored accordingly. Due to the difference in physicochemical properties of both antimicrobial polymers and agents, the antimicrobial mechanism could be demonstrated by antimicrobial agent release, antimicrobial agent retention, contact-killing, and anti-adhesion. This paper provides information on antimicrobial coatings, in terms of the synthesis methods, antimicrobial mechanism, influencing factors, and applications in various industries.
Keywords: Antimicrobial coatings; Antimicrobial activity; Influencing factors; Mechanism; applications